Three-Phased Risk-Management Benchmark for Internationalization of Small and Medium-Sized Construction Companies - Jung, Wooyong; Han, Seung Heon; Park, Chanyoung; Lee, Changjun; Baek, Seungwon (KSCE journal of civil engineering, 2022)
Small and medium-sized construction companies (SMCCs) typically lack the international experience of their large counterparts. International construction projects often are more uncertain than domestic projects, which can pique SMCCs’ interest or necessity for external benchmarks of best practices. This study aims to provide a three-phased risk-management benchmark framework for the internationalization of SMCCs. The first-phase benchmarking evaluates how well companies prepare to undertake business abroad and what capabilities they should improve upon based on comparative data from 41 SMCCs. The second-phase benchmarking provides risk information from 49 international subcontract projects that must be managed for SMCCs. In the last phase, the benchmark delivers subcontractor risk-response strategies through the analysis of 134 international-contractual cases. Additionally, the three illustrative cases show that the benchmark framework and metrics are quite helpful for decision-makers and SMCC practitioners in evaluating and responding to their international construction project risks.